Doktrin Kenabian Ahmadiyah Perspektif Teologis dan Analisis Sejarah Kemunculan - Moh Muhtador (JUSPI (Jurnal Sejarah Peradaban Islam), 2021)
This article specifically discusses the meaning of the prophet for the Ahmadiyya community. Ahmadiyya is a religious group that still believes in the existence of the status of the last prophet, apart from the Prophet Muhammad who is believed by the majority of Muslims. The purpose of this article is to find out the doctrine of prophethood from the perspective of theology and the history of the emergence of prophetic meaning among Ahmadiyya. This research is a qualitative study that takes references from the internal literature of the Ahmadiyya congregation as well as secondary ones related to the insight into the meaning of prophethood. The theory used is the hermeneutical-interpretation-analysis theory to get a picture of Ahmadiyya's understanding of the meaning of prophethood, so that the Ahmadiyya congregation believes in the meaning of prophethood inclusively inherent in elected people, such as the presence of Mirza Ghulam Ahmad with a prophetic status to continue the teachings of the previous prophet, namely Prophet Muhammad. This is due to the history of Islamic politics at that time in India which demanded a new reading of the meaning of prophethood.